Empirical study on how social media promotes product innovation - Hiroki Idota; Teruyuki Bunno; Masatsugu Tsuji (International Telecommunications Society (ITS), 2014)
Social media such as SNS, Twitter, and the blogs has been spreading all over the world, and a large number of firms recognize social media as new communication tools for obtaining information on consumer needs and market for developing new goods and services and promoting marketing. In spite of increasing its use in the reality, academic research on whether or how social media contributes to promoting product innovation is not enough yet. This study thus attempts to analyze empirically how social media use enhances product innovation based on the survey data to Japanese firms using statistical method such as ordered probit analysis. This study finds that consumers' cooperation via social media is indispensable for effective social media use of firms. All of three managerial orientations such as prototyping, corporate initiatives, and cooperation with consumers are effective to using social media for innovation. Firms use social media effectively for communicating tools not only outside but also inside the firm. Social media is found to support firms to obtain the market trend, and consumer needs and reputation of existing products, and to promote product innovation.
Keywords: 330; social media; product Innovation; ordered probit analysis; factor analysis; R&D orientation